2019
DOI: 10.3390/polym11111861
|View full text |Cite
|
Sign up to set email alerts
|

In-Vitro Hemocompatibility of Polyaniline Functionalized by Bioactive Molecules

Abstract: Hemocompatibility is an essential prerequisite for the application of materials in the field of biomedicine and biosensing. In addition, mixed ionic and electronic conductivity of conducting polymers is an advantageous property for these applications. Heparin-like materials containing sulfate, sulfamic, and carboxylic groups may have an anticoagulation effect. Therefore, sodium dodecylbenzenesulfonate, 2-aminoethane-1-sulfonic acid and N-(2-acetamido)-2-aminoethanesulfonic acid were used for modification of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Among the multitude of functionalized polyanilines are halogenated PANI [ 182 , 183 ], carboxylic, sulfonic and sulfamic derivatives of PANI [ 184 ], and butylthio-functionalized PANI [ 185 ]. Both the protonated and non-protonated forms of PANI will undergo changes in band gaps, highest occupied molecular orbital (HOMO), and lowest unoccupied molecular orbital (LUMO).…”
Section: Materials Design Approach For Unique Hydration Propertiesmentioning
confidence: 99%
“…Among the multitude of functionalized polyanilines are halogenated PANI [ 182 , 183 ], carboxylic, sulfonic and sulfamic derivatives of PANI [ 184 ], and butylthio-functionalized PANI [ 185 ]. Both the protonated and non-protonated forms of PANI will undergo changes in band gaps, highest occupied molecular orbital (HOMO), and lowest unoccupied molecular orbital (LUMO).…”
Section: Materials Design Approach For Unique Hydration Propertiesmentioning
confidence: 99%
“…In addition, mixed ionic and electronic conductivity of conducting polymers is an advantageous property for these applications. The results showed that the anticoagulation activity was highly affected by the presence of suitable functional groups originating from the used heparin-like substances and by the properties of the polyaniline polymer itself [29].…”
mentioning
confidence: 99%